Confirmatory analysis of a health state classification system for people living with dementia: a qualitative approach. Issue 4 (October 2019) - Welch, Alyssa; Kim-Huong, Nguyen; Quinn, John; Gregory, Caroline; Moyle, Wendy; Ratcliffe, Julie; Comans, Tracy
Objectives: This paper aims to confirm the content validity of the domains identified during the development of the Alzheimer's disease – five dimensions (AD-5D) algorithm for the quality of life – Alzheimer's disease (QOL-AD) and to identify the rationale for stated quality of life preferences. Methods: Focus groups were conducted to elicit the priorities for quality of life in dementia from three perspectives: the person with dementia; family caregivers; and the community. Participants were recruited through industry research partners (long-term care providers) based on knowledge of their experience with dementia. Three focus groups were conducted – one each in Brisbane, Sydney and Adelaide, Australia – between November 2016 and February 2017. Each focus group included participants providing a different perspective on dementia – people with dementia ( n = 3), caregivers ( n = 9) and general community members or relatives of residents of a long-term care facility ( n = 10), although some groups contained one participant with a different perspective. The focus groups were used to validate the AD-5D domains and examine quality of life preferences across the three perspectives. Thematic analysis was used to identify the priorities underlying preference selection. Results: All activities affecting the quality of life for people with dementia could be mapped to one of the five AD-5D domains: memory, mood, physical health, living situation and ability to do things for fun. The domains considered most important for quality of life differed between people with dementia, their caregivers and members of the community, with memory the least important domain for all three groups. The rationale for priorities also varied between groups. Conclusions: This study confirmed the content validity of the selection of the AD-5D domains and identified multiple differences in the reasons behind stated priorities for quality of life for people with dementia, their caregivers and community members.